Honey bee‐collected pollen in agro‐ecosystems reveals diet diversity, diet quality, and pesticide exposure. Issue 18 (5th August 2017) - Colwell, Megan J.; Williams, Geoffrey R.; Evans, Rodger C.; Shutler, Dave
Abstract: European honey bees Apis mellifera are important commercial pollinators that have suffered greater than normal overwintering losses since 2007 in North America and Europe. Contributing factors likely include a combination of parasites, pesticides, and poor nutrition. We examined diet diversity, diet nutritional quality, and pesticides in honey bee‐collected pollen from commercial colonies in the Canadian Maritime Provinces in spring and summer 2011. We sampled pollen collected by honey bees at colonies in four site types: apple orchards, blueberry fields, cranberry bogs, and fallow fields. Proportion of honey bee‐collected pollen from crop versus noncrop flowers was high in apple, very low in blueberry, and low in cranberry sites. Pollen nutritional value tended to be relatively good from apple and cranberry sites and poor from blueberry and fallow sites. Floral surveys ranked, from highest to lowest in diversity, fallow, cranberry, apple, and blueberry sites. Pesticide diversity in honey bee‐collected pollen was high from apple and blueberry sites and low from cranberry and fallow sites. Four different neonicotinoid pesticides were detected, but neither these nor any other pesticides were at or above LD50 levels. Pollen hazard quotients were highest in apple and blueberry sites and lowest in fallow sites. Pollen hazard quotients were also negatively correlated with the number of flower taxa detected in surveys. Results reveal differences among site types in diet diversity, diet quality, and pesticide exposure that are informative for improving honey bee and land agro‐ecosystem management. Abstract : Honey bees have been suffering economically unsustainable overwintering losses since 2007 in North America and Europe. In four different site types, we evaluated whether nutrition and pesticides in honey bee‐collected pollen were contributing to these disturbing losses. We found that honey bees collected all their pollen from noncrop sources when deployed in blueberries, that nutrition in honey bee‐collected pollen was poor when they were deployed in blueberries, and that pesticide exposure varied among deployments but were collectively below LD50 levels.